The Effects of Revenue and Social Capital on Collective Governance: Implications for Political Complexity. (October 2018) - Freeman, Jacob; Keith, Jonathan; Roberts, Max; Owens, Andrew
We evaluate two models that may explain variation in the inclusiveness of governments and their ability to provision public goods. The revenue model predicts that a government's source of revenue determines whether elites invest in effective bureaucracy and the provision of public goods that benefit wide swaths of society or the extraction of resources from society to benefit a limited network. In this model, a cooperative society with high social capital is an outcome of effective, collective government. The combined model predicts that social capital has a semi-independent causal effect, in addition to revenue, on the inclusiveness of governments. Our results indicate that the combined model of collective governance fits the data on U.S. states better than the revenue model alone. The combined model of governance predicts that revenue and social capital moderate the population size–political complexity relationship, and data from the U.S. states are consistent with these predictions.